Growth and Yield of Soybean Genotypes as Influenced by Sowing Time at Different Locations under Climate Change Situation in Maharashtra, India - Kathmale, D. K.; Andhale, A. U.; Deshmukh, M. P. (International Journal of Bio-resource and Stress Management, 2023)
An experiment was taken up at five locations viz. K. Digraj (Dist: Sangli), Karad (Dist: Satara, Gadhinglaj (Dist: Kolhapur), Savalvihir (Dist: Ahmednagar) and Jalgaon in a Split plot design with three replications. Main plot treatments comprised different five sowing dates from 25th June to 5th August with 10 days interval and sub plot treatments were different nine genotypes viz., JS 335, P. Kalyani, MACS 450, MAUS 71, KDS 321, KDS 344, KDS 345, KDS 347 and KDS 378. The results revealed that at all the locations, significantly higher soybean grain yield was noticed in first two sowing dates i.e., on 25th June and 5th July, however, drastic reduction in grain yield (15.82 q ha-1) was witnessed under delayed sowing conditions (15th July to 5th Aug). Over the locations, the genotype KDS 347 performed better and recorded average yield of 20.84 q ha-1. At Digraj, highest grain yield was recorded by the genotype KDS-378 (27.95 q ha-1) and at Karad, highest grain yield (35.56 q ha-1) was recorded by MACS-450. At Gadhinglaj, different genotypes did not differ significantly in respect of mean soybean grain yield. At Savalvihir, the genotype KDS-378 recorded grain yield increase to the tune of 19.35% over all other genotypes tested. At Jalgaon, highest grain yield of soybean was recorded by KDS-321 (14.76 q ha-1). The sowing of soybean should not be delayed after 5th July in Southern Maharashtra and genotypes like KDS 347, KDS 378, MAUS 71 and MACS 450 are preferred for higher yield.